Visualizing arthritic inflammation and therapeutic response by fluorine-19 magnetic resonance imaging (19F MRI) - Balducci Anthony; Helfer Brooke M; Ahrens Eric T; O'Hanlon Charles F; Wesa Amy K (BMC, 2012)
Abstract Background Non-invasive imaging of inflammation to measure the progression of autoimmune diseases, such as rheumatoid arthritis (RA), and to monitor responses to therapy is critically needed. V-Sense, a perfluorocarbon (PFC) contrast agent that preferentially labels inflammatory cells, which are then recruited out of systemic circulation to sites of inflammation, enables detection by 19F MRI. With no 19F background in the host, detection is highly-specific and can act as a proxy biomarker of the degree of inflammation present. Methods Collagen-induced arthritis in rats, a model with many similarities to human RA, was used to study the ability of the PFC contrast agent to reveal the accumulation of inflammation over time using 19F MRI. Disease progression in the rat hind limbs was monitored by caliper measurements and 19F MRI on days 15, 22 and 29, including the height of clinically symptomatic disease. Naïve rats served as controls. The capacity of the PFC contrast agent and 19F MRI to assess the effectiveness of therapy was studied in a cohort of rats administered oral prednisolone on days 14 to 28. Results Quantification of 19F signal measured by MRI in affected limbs was linearly correlated with disease severity. In animals with progressive disease, increases in 19F signal reflected the ongoing recruitment of inflammatory cells to the site, while no increase in 19F signal was observed in animals receiving treatment which resulted in clinical resolution of disease. Conclusion These results indicate that 19F MRI may be used to quantitatively and qualitatively evaluate longitudinal responses to a therapeutic regimen, while additionally revealing the recruitment of monocytic cells involved in the inflammatory process to the anatomical site. This study may support the use of 19F MRI to clinically quantify and monitor the severity of inflammation, and to assess the effectiveness of treatments in RA and other diseases with an inflammatory component.